2003
DOI: 10.1007/bf02660771
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic antigen mrna in the mesenteric vein is not a predictor of hepatic metastasis in patients with resectable colorectal cancer

Abstract: This study failed to demonstrate the high predictive value of carcinoembryonic antigen messenger ribonucleic acid detection in the draining venous blood for the development of hepatic metastases. However, the authors demonstrated that the presence of cancer cells in the draining venous blood was the essential and initial step to the development of hepatic metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Our data agrees with recent RT-PCR studies showingthatpatientspositiveforCEAorCK20mRNAhada significantlypoorerprognosisthanpatientsnegativeforthese markers [3,5,19]. HighlevelsofpreoperativeCEAareasignificantnegative prognosticmarkerforreducedoverallsurvivalaftersurgical resection of colorectal carcinomas [8,9,15], though CEA mRNA was not predictive for the development of hepatic metastasis [20].AlthoughCEAandCK20mRNAlevelswere higher in colorectal tumors when compared to non-tumor tissue, they were not related to staging or clinical development [21].PostoperativeCEAlevels,butnotCA19-9orp53 levels, were a significant prognostic factor for disease-free survivalofCRCpatients [22].Ourstudypopulationincluded 27postoperativepatientsand19patientswithorganmetasta-sesthatcouldnotbesurgicallyremoved.Patientspositivefor CEA mRNA had significantly shorter survival curves than thosenegativeforCEAmRNA,thoughCK20mRNA,serum CEAproteinlevels,andserumCA19-9proteinlevelshadno correlationwithoverallsurvival.Wesuggestthatthiscouldbe due to i) the small study population or ii) admixture of patientsatdifferentstagesofthedisease.WenotedthatCEA mRNAwashigherinstageIpatientsthaninstageIIpatients andwaspresentinsomeofthehealthyvolunteers,thoughwe donotcurrentlyhaveanexplanationforthis.However,CRC diagnosiswasnotbasedonCEAmRNAlevelsbutonpathologicalfindings.…”
Section: Survivalsupporting
confidence: 80%
“…Our data agrees with recent RT-PCR studies showingthatpatientspositiveforCEAorCK20mRNAhada significantlypoorerprognosisthanpatientsnegativeforthese markers [3,5,19]. HighlevelsofpreoperativeCEAareasignificantnegative prognosticmarkerforreducedoverallsurvivalaftersurgical resection of colorectal carcinomas [8,9,15], though CEA mRNA was not predictive for the development of hepatic metastasis [20].AlthoughCEAandCK20mRNAlevelswere higher in colorectal tumors when compared to non-tumor tissue, they were not related to staging or clinical development [21].PostoperativeCEAlevels,butnotCA19-9orp53 levels, were a significant prognostic factor for disease-free survivalofCRCpatients [22].Ourstudypopulationincluded 27postoperativepatientsand19patientswithorganmetasta-sesthatcouldnotbesurgicallyremoved.Patientspositivefor CEA mRNA had significantly shorter survival curves than thosenegativeforCEAmRNA,thoughCK20mRNA,serum CEAproteinlevels,andserumCA19-9proteinlevelshadno correlationwithoverallsurvival.Wesuggestthatthiscouldbe due to i) the small study population or ii) admixture of patientsatdifferentstagesofthedisease.WenotedthatCEA mRNAwashigherinstageIpatientsthaninstageIIpatients andwaspresentinsomeofthehealthyvolunteers,thoughwe donotcurrentlyhaveanexplanationforthis.However,CRC diagnosiswasnotbasedonCEAmRNAlevelsbutonpathologicalfindings.…”
Section: Survivalsupporting
confidence: 80%
“…These results are in accordance with the ones reported by Taniguchi et al [16] who found that the positive rates of CEA mRNA increased significantly in patients with lymph node metastases and with lymphatic invasion. On the other hand, there are studies where no correlation could be detected between the presence of CEA mRNA and any clinicopathological factors including the ones mentioned above [20,25].…”
Section: Discussionmentioning
confidence: 92%
“…Akashi et al [25] in a study containing 80 patients, failed to demonstrate a high predictive value of CEA mRNA detection in the draining venous blood for the development of hepatic metastases. In his study, 80% of patients with positive CEA mRNA did not have hepatic metastases after surgery.…”
Section: Discussionmentioning
confidence: 94%
“…27,28 Moreover, some investigators reported no appreciable difference between d-CEA levels and CEA mRNA expression. 28,29 Thus, the signifi cance of the d-CEA level remains open to debate.…”
Section: Discussionmentioning
confidence: 98%